ECONOMIC POTENTIAL ANALYSIS IN BLITAR REGENCY 2015-2020 - Yopy Pandhu Lintang Gumelar; Arfida Boedirochminarni; Dwi Susilowati (EP FEB UNS, 2023)
This study aims to identify the basic and non-basic economic sectors, determine leading sectors, and analyze sectoral growth patterns in Blitar Regency from 2015 to 2020. The research utilizes a quantitative descriptive approach, drawing on secondary data sources. Techniques employed include Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Klassen Typology. The findings reveal that Blitar Regency has 8 basic sectors and 9 non-basic sectors. Additionally, the LQ and DLQ analysis identifies 7 leading sectors, 9 developing sectors, and 1 potential sector. The Klassen Typology further categorizes the sectors into 3 rapidly growing and advanced sectors, 6 advanced but declining sectors, 2 fast-growing sectors, and 6 underdeveloped sectors.